The Effect of Self-Efficacy and Social Support on Academic Adjustment through Academic Resilience - Raju Ahmad Ghifari; Layyinah Layyinah (Research Horizon, 2026)
Academic adjustment is a crucial determinant of undergraduate success, particularly during the transition to higher education, where students often face increased academic demands and psychological pressures. This study aims to examine the effects of self-efficacy and social support on academic adjustment, with academic resilience as a mediating variable among first-year undergraduate students. A quantitative correlational design with path analysis was employed, involving 285 university students. Data were collected using standardized questionnaires and analyzed using SPSS 26 and Mplus 8.4. The findings reveal that self-efficacy and social support significantly influence academic adjustment both directly and indirectly through academic resilience. Academic resilience was found to play a significant mediating role in strengthening students’ ability to adapt to academic demands. The results indicate that students with higher self-efficacy and stronger social support tend to demonstrate better academic adjustment, supported by greater resilience in facing academic challenges. In conclusion, academic adjustment is shaped by the interplay of internal and external factors through psychological resilience mechanisms. These findings imply that universities should develop intervention programs focusing on enhancing self-efficacy, strengthening social support systems, and fostering academic resilience to improve student adaptation and reduce dropout risk.